Identification of Foot and Mouth Disease (FMD) Virus From Recently Outbreak Crossbred Cattle In Rajbari District of Bangladesh (SAARC Journal of Agriculture, 2021)
Foot and mouth disease (FMD) is a devastating viral disease and endemic in nature in Bangladesh that causes huge economical losses. The present research work was aimed to determine the prevalence of FMD outbreaks and molecular detection of FMDV serotypes by uRT-PCR and gsRT-PCR test, respectively from crossbred cattle in the Rajbari district of Bangladesh during the period from January to June 2018. A total of 16 tongue epithelial samples were collected from clinically FMD suspected 2 to 3 years old crossbred cattle. 14 samples were positive by uRT-PCR. The detection rate of FMDV by uRT-PCR was 87.50%. Then uRT-PCR positive samples were serotype by gsRT-PCR. Serotype based prevalence of FMDV was 42.86%, 100%, 21.43% and 21.43% in O serotype, Asia-1 serotype, A serotype and mixed infection with Asia-1 and A, respectively. Considering the age, the prevalence of confirmed FMD outbreak was 42.86%, 35.71% and 21.43% at the age of 2, 2.5 and 3 years, respectively. Serotype A, O and Asia-1 is circulated in Rajbari district and required trivalent vaccine for prevention and control of FMD in that area.SAARC J. Agric., 19(1): 201-210 (2021)